2021
DOI: 10.3390/molecules26082229
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Polymeric Nanosystems against Oral Diseases

Abstract: Nanotechnology and nanoparticles (NPs) are at the forefront of modern research, particularly in the case of healthcare therapeutic applications. Polymeric NPs, specifically, hold high promise for these purposes, including towards oral diseases. Careful optimisation of the production of polymeric NPs, however, is required to generate a product which can be easily translated from a laboratory environment to the actual clinical usage. Indeed, considerations such as biocompatibility, biodistribution, and biodegrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 186 publications
0
3
0
Order By: Relevance
“…Even while recent algorithms have demonstrated that there are considerable connections between the human intestinal microbiota and colonic illnesses, very little can be mentioned regarding how the metabolic activities and gene mutations of the microbial community impact colon tissue growth. [224]. This is still the case.…”
Section: Future Concepts and Opinions Examinedmentioning
confidence: 92%
“…Even while recent algorithms have demonstrated that there are considerable connections between the human intestinal microbiota and colonic illnesses, very little can be mentioned regarding how the metabolic activities and gene mutations of the microbial community impact colon tissue growth. [224]. This is still the case.…”
Section: Future Concepts and Opinions Examinedmentioning
confidence: 92%
“…The expression “molecular recognition” has seen increased use since the early 1980s, specifically indicating a group of phenomena driven by ad hoc physicochemical interactions (mainly noncovalent) [ 1 ]. These phenomena are critical for certain biological processes (e.g., ligand-receptor interactions), and a significant proportion of current research in chemistry, materials as well as pharmaceutical areas is indeed driven by the possibility of designing and tailoring specific molecular interactions suitable to be successfully employed in the desired applications [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a burst release of drug is frequently observed in conventional polymeric vehicles, thus resulting in potentially severe consequences for the patients such as toxicity issues and undesirable side effects caused by temporarily high-drug dosage [5]. To date, although improved polymeric vehicles have been developed, some key knowledge gaps in terms of toxicity, physicochemical instability and lack of stimuli-responsiveness have been limitedly addressed, thus hindering practical applications [17][18][19]. On average, only one of the 5000 polymer-based DDSs that enters preclinical studies turns into an approved dosage form after~10 years (from the initial conception to the market approval) [20].…”
Section: Introduction 1drug Delivery Systemsmentioning
confidence: 99%